Potential use of polyacrylamide for soil erosion control in Brazil - Silva, Alexandre Marco da [UNESP]; Durrant, Steven Frederick [UNESP] (Canadian Center of Science and Education, 2010)
Since soil erosion is currently a worldwide threat, its control has become a necessity. The performance and effectiveness of synthetic organic polymers such polyacrylamide (PAM), have been intensively studied, especially for erosion control in temperate climate conditions. In tropical regions, however, where climatic conditions are usually severe, very little research has been conducted. The Brazilian region is a good example, where few papers on this subject exist. In addition to the severe climatic conditions, careless land use has been prevalent for many years. The use of PAM for erosion control in Brazilian soils may be a good option to minimize the impacts of the soil degradation process, but more research is required to optimize its application.
Keywords: Soil erosion control; Brazilian soils; Polyacrylamide